(untitled) (Journal of Educational Sciences, 2022)
The article deals with the main problems of inclusive education of children with special learning needs related to health characteristics. The relevance of the topic is due to the current update of the existing education system aimed at organizing conditions for co-education of children with disabilities (LHO) with children without special educational needs, insufficient development of the methodology of inclusive education in the Republic of Kazakhstan. The purpose of the study is the theoretical and practical justification of the applied pedagogical technologies of inclusive education in Kazakhstan, generalization of the innovative author’s experience of individualized work with children with disabilities in the construction of an inclusive lesson model. The results of the theoretical analysis of the use of pedagogical technologies in inclusive education, considered in the scientific works of domestic and foreign scientists, are presented. The author describes the peculiarities of perception and memorization of the received information in children with disabilities, analyzes the methodological and organizational aspects of the implementation of individualized work with children with disabilities. The methodology of the lessons conducted with children with hearing and speech disorders in the framework of the autumn IT school is summarized. 13 students of the State Educational Institution «Special comprehensive boarding School No. 1 for children with hearing and speech disorders» of Pavlodar and ordinary children took part in the empirical work. The innovative component includes the use of didactic video material developed in the Vectorian Giotto multimedia program. Methodological recommendations are proposed that reveal the features of the organization of lessons in inclusive education in conditions of all levels of education, new pedagogical technologies of the organization of co-education are presented. Key words: inclusive learning; collaborative learning; adaptive learning system; individualized learning; student; teacher.